Implikasi Pendidikan Agama Islam dan Responsi terhadap Keaktifan Salat Berjamaah Mahasiswa di Fakultas Ekonomi dan Bisnis, Universitas Medan Area - Fauji Wikanda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
This study aims to determine the implementation of Islamic religious education courses and responsiveness and their implications for the activity of the prayer of the students in the Faculty of Economics, University of Medan Area. This study uses a qualitative method. The process of collecting research data uses qualitative analysis techniques with steps to explain data and draw conclusions. Based on data in the field and analysis, this study found: First, the implementation of Islamic religious education includes goals, curriculum, teaching and learning process, evaluation and responsiveness of Islamic religious education courses. Second, the activeness of the prayers in the congregation of students at the campus mosque is the result of the activities of the Islamic religious education courses conducted by lecturers of Islamic religious education courses.